Initial development of Combretum leprosum Mart. seedlings irrigated with saline water of different cationic natures - Leal, Caio César; Dantas, Nadjamara; Torres, Salvador; Vale, Amsterdam; Freitas, Rômulo (Revista Ciência Agronômica, 2019)
This study aimed to evaluate the tolerance of C. leprosum seedlings to salt stress during the emergence and early seedling development. The experiment was carried out between the months of August and September, in a greenhouse, and the substrate used was the commercial coconut fiber wetted with aqueous solutions of sodium chloride (NaCl), calcium chloride (CaCl2) and potassium chloride (KCl) with the electrical conductivities of 0.0, 1.5, 2.5, 3.5, 4.5, 5.5 and 6.5 dS m-1. We used a completely randomized design in a 3 x 7 factorial scheme (three salts x seven levels of electrical conductivity). We evaluated seedling emergence, emergence speed index, root length, shoot length, dry matter of roots and shoots. The results indicated significant interaction between both factors analyzed. The emergence and initial growth of C. leprosum plants decrease gradually due to the increase of the electrical conductivity levels, with root length being less affected by waters salinized with CaCl and KCl. C. leprosum seedlings show sensitivity to the three types of salts and are highly sensitive to KCl and NaCl.